Observation of a photoinduced, resonant tunneling effect in a carbon nanotube–silicon heterojunction - Aramo, Carla (Beilstein J Nanotechnol, 2015)
A significant resonant tunneling effect has been observed under the 2.4 V junction threshold in a large area, carbon nanotube–silicon (CNT–Si) heterojunction obtained by growing a continuous layer of multiwall carbon nanotubes on an n-doped silicon substrate. The multiwall carbon nanostructures were grown by a chemical vapor deposition (CVD) technique on a 60 nm thick, silicon nitride layer, deposited on an n-type Si substrate. The heterojunction characteristics were intensively studied on different substrates, resulting in high photoresponsivity with a large reverse photocurrent plateau. In this paper, we report on the photoresponsivity characteristics of the device, the heterojunction threshold and the tunnel-like effect observed as a function of applied voltage and excitation wavelength. The experiments are performed in the near-ultraviolet to near-infrared wavelength range. The high conversion efficiency of light radiation into photoelectrons observed with the presented layout allows the device to be used as a large area photodetector with very low, intrinsic dark current and noise.